PHYSICAL ACTIVITY DETERMINANTS AMONG ADULT OBESITY BASED ON PENDER’S HEALTH PROMOTION MODEL - Dini Tryastuti; Karyadi; Uswatun Khasanah; Andina Nursyifa Tresna; Moh Fuad Almubarok (NURSE: Journal of Nursing and Health Science, 2025)
Background: Based on data from the 2018 Basic Health Research (Riskesdas) groups of adolescents to adults have sedentary lifestyles (sedentary / lack of physical activity) of 33,5%. Lack of physical activity can lead to health risks especially the complications of non-communicable. This study aims to determine the relationship of physical activity and its determinants among adult obesity. Methods : This study uses a quantitative method with a cross-sectional study design. A total of 262 adult obesity in ciputat  timur participated in this study. Data collected by filling out the questionnaire by participant. Data analysis used the chi square test to determine the relationship between physical activity and its determinants and logistic regression to determine the predictors of physical activity. Results: This study provides results that  Respondents who have low physical activity was 64,6%. There is a significant relationship between gender, perceived benefit, perceived barrier, self efficacy and social support. Conclutions: In conclusion, the most significant determinant of physical activity in the adult obesity is social support. Therefore, this study's results may contribute to planning interventions and strategies aiming to promote physical activity participation among  adults. Keywords : Physical Activity, Determinant of physical activity, social support, adult obesity